Evaluation of the interest to combine a CD4 Th1-inducer cancer vaccine derived from telomerase and atezolizumab plus bevacizumab in unresectable hepatocellular carcinoma: a randomized non-comparative phase II study (TERTIO – PRODIGE 82) - Angélique Vienot; Marion Jacquin; Magali Rebucci-Peixoto; Dimitri Pureur; François Ghiringhelli; Eric Assenat; Pascal Hammel; Olivier Rosmorduc; Morgane Stouvenot; Manon Allaire; Mohamed Bouattour; Hélène Regnault; et al. (BMC Cancer, 2023)
Abstract Background Several cancer immunotherapies that target the PD-L1/PD-1 pathway show promising clinical activity in patients with hepatocellular carcinoma (HCC). However, the standard of care in first-line treatment with atezolizumab (anti-PD-L1 therapy) in combination with bevacizumab is associated with a limited objective response rate. Telomerase reverse transcriptase (TERT) activation meets the criteria of oncogenic addiction in HCC and could be actionable therapeutic target and a relevant tumor antigen. Therefore we hypothesized that combining anti-PD-1/PD-L1 therapy with an anti-telomerase vaccine might be an attractive therapy in HCC. UCPVax is a therapeutic cancer vaccine composed of two separate peptides derived from telomerase (human TERT). UCPVax has been evaluated in a multicenter phase I/II study in non–small cell lung cancers and has demonstrated to be safe and immunogenic, and is under evaluation in combination with atezolizumab in a phase II clinical trial in tumors where telomerase reactivation contributes to an oncogene addiction (HPV+ cancers). The aim of the TERTIO study is to determine the clinical interest and immunological efficacy of a treatment combining the CD4 helper T-inducer cancer anti-telomerase vaccine (UCPVax) with atezolizumab and bevacizumab in unresectable HCC in a multicenter randomized phase II study. Methods Patients with locally advanced, metastatic or unresectable HCC who have not previously received systemic anti-cancer treatment are eligible. The primary end point is the objective response rate at 6 months. Patients will be allocated to a treatment arm with a randomization 2:1. In both arms, patients will receive atezolizumab at fixed dose of 1200 mg IV infusion and bevacizumab at fixed dose of 15 mg/kg IV infusion, every 3 weeks, according to the standard of care. In the experimental arm, these treatments will be combined with the UCPVax vaccine at 0.5 mg subcutaneously. Discussion Combining anti-PD-1/PD-L1 therapy with an anti-telomerase vaccine gains serious consideration in HCC, in order to extend the clinical efficacy of anti-PD-1/PD-L1. Indeed, anti-cancer vaccines can induce tumor-specific T cell expansion and activation and therefore restore the cancer-immunity cycle in patients lacking pre-existing anti-tumor responses. Thus, there is a strong rational to combine immune checkpoint blockade therapy and anticancer vaccine (UCPVax) in order to activate antitumor T cell immunity and bypass the immunosuppression in the tumor microenvironment in HCC. This pivotal proof of concept study will evaluate the efficacy and safety of the combination of a CD4 Th1-inducer cancer vaccine derived from telomerase (UCPVax) and atezolizumab plus bevacizumab in unresectable HCC, as well as confirming their synergic mechanism, and settling the basis for a new combination for future clinical trials. Trial registration NCT05528952.